Redistribucijski učinci socijalnih transfera u Republici Hrvatskoj - Babić, Zdenko (Array, 2008)
The paper analytically investigates the system of social transfers in Croatia and evaluates their impact on reducing poverty and economic inequality in Croatia. In the theoretical part of the paper, recent results from the economic research studies about the new role of social expenditure and social transfers in the new environment are presented. The survey of recent literature questions the view of some schools of the economic thoughts about the role of social expenditure, that claim that social expenditure is not productive and jeopardizes economic development. The research results show that the Croatian system of social transfers is contributing to both poverty and economic inequality reduction in Croatia, but the effi ciency of the system is slightly below European average. The conclusion is that there is a space for improvement regarding the effi ciency of the social transfer system. The best-rated transfers regarding their contribution to poverty reduction are social assistance and family pensions. However, the social assistance level and the coverage rate of the poor receiving social assistance in Croatia are low. That fact and the effi ciency problems in the social transfer system partially explain why the process of relatively intense economic development in Croatia over the last decade has not contributed to the increase of material well being of the poor in Croatia